Expression of fibroblast growth factor 21 in the liver of dairy cows in the transition period and during lactation. Issue 5 (17th July 2012) - Schlegel, G.; Ringseis, R.; Keller, J.; Schwarz, F. J.; Windisch, W.; Eder, K.
Summary: Fibroblast growth factor 21 (FGF21) has been identified as a novel hormonal factor involved in the regulation of metabolic adaptations during energy deprivation. The present study aimed to investigate the expression of the FGF21 gene in the liver of dairy cows during the transition from pregnancy to lactation. Therefore, the relative mRNA abundance of FGF21 in liver biopsy samples of 20 dairy cows in late pregnancy (3 weeks pre‐partum) and early lactation (1, 5, 14 weeks post‐partum) was determined. It was observed that hepatic mRNA abundance of FGF21 at 1 week post‐partum was dramatically increased (110‐fold) compared to 3 weeks pre‐partum (p < 0.001). With progress of lactation, mRNA concentration of FGF21 was declining; nevertheless, mRNA abundance at 5 and 14 weeks post‐partum remained 25‐ and 10‐fold increased compared to 3 weeks pre‐partum (p < 0.001). Using a gene array technique, it was found that many genes involved in fatty acid oxidation, gluconeogenesis and ketogenesis were up‐regulated during early lactation compared to late pregnancy. Moreover, there were positive linear correlations between hepatic mRNA concentration of FGF21 and mRNA concentrations of genes involved in ketogenesis as well as carnitine synthesis and carnitine uptake at various time‐points during lactation, indicating that FGF21 could play a role in ketogenesis and carnitine metabolism in the liver of dairy cows (p < 0.05). In overall, the present study shows that expression of the FGF21 gene is strongly up‐regulated during the transition period. It is assumed that the up‐regulation of FGF21 might play an important role in the adaptation of liver metabolism during early lactation in dairy cows such as in other species.